Making a Makerspace: Identified Practices in the Formation of a University Makerspace. Issue 1 (2nd January 2021) - Tomko, Megan E.; Nagel, Robert L.; Newstetter, Wendy; Smith, Shaunna F.; Talley, Kimberly G.; Linsey, Julie
Abstract : This study seeks to understand the origin accounts of academic makerspaces targeted for engineering students at higher education institutions, as described from the perspective of those who played a formative role in the development of the university's makerspace. The origin accounts of eight varied university makerspaces are investigated for their practices (or shared strategies) in the formation of a university makerspace. This study implements a semi-structured interview protocol focused on the topics of administration, access, design, and aspects unique to the makerspace. Nine leaders from eight U.S. university makerspaces participated in this study. The interview data were analysed through multiple cycles of coding, and four major themes emerged: a need allowed for a want (and vice versa ), access allowed for varied learning opportunities, direction allowed for empowerment, and experimentation allowed for sustainability. To supplement the four major themes, this article presents makerspace profiles and summaries of how each space started along with a comparison chart that reports the type of institution, funding sources, access, and management models. Through juxtaposing the makerspace profiles with the emergent themes, this article provides transferrable insights regarding operational practices for academic makerspaces.